The empirical examination of changes related to value drivers in the effects of the 2007-2008 crisis - Kiss, Anita (Applied Studies in Agribusiness and Commerce, 2016)
The article brings into the focus the corporate value creation and the main value drivers. The first goal of the study is to classify the most relevant value drivers, and their function of the firms’ value. Further objective of this paper is to present the effects of the 2007-2008 global financial crisis. This article demonstrates the following. The first part introduces the value chain and illustrates the primary and the support activities of the companies. The second section briefly presents the 2007-2008 global economic crisis, introducing its causes, events and financial aspects. The third empirical part of the paper analyses the database featuring data from 18 European countries, 10 sectors and 1553 firms in the period between 2004 and 2011. At the end, the fourth part contains conclusions. Based on the related literature reviewed and in the conducted empirical research it can be assessed that 2008 can be seen unambiguously as the year of the crisis. In this year, all independent variables had a negative effect on the dependent variable.JEL code: P40